ChemInform Abstract: Asymmetric Synthesis of α‐Alkylidene‐β‐hydroxy‐γ‐butyrolactones via Enantioselective Tandem Michael—Aldol Reaction. Issue 22 (13th May 2013) - Lee, Sung Il; Jang, Jin Hee; Hwang, Geum‐Sook; Ryu, Do Hyun
Abstract This is a simple and efficient method for the asymmetric synthesis of the title compounds (V), a common motif in natural products.